CLONING OF NOVEL BEMYB680 TRANSCRIPTIONAL FACTOR FROM BAMBUSA EMEIENSIS; CANVASSING TRANSACTIVATION ANALYSIS AND GENE EXPRESSION PROFILING IN THE PANORAMA OF DIFFERENT ABIOTIC STRESSES - M. Imran; N. Samo; S. L. Hu; X. G. Luo; Y. Cao; Y. Huang; S. Ahmed; D. Y. Gong (Journal of Animal and Plant Sciences, 2019)
In this study MYB family related transcription factor (TF) was cloned and characterized from Bambusa emeiensis and tentatively named as “BeMYB680”. We selected the TFs from bamboo because of its potentials for future improvement in terms of transgenic plants. Bamboo is fast-growing species and provides a very good podium because of its adoptable genomics to harsh climatic conditions. The BeMYB680 was sequenced (Liuhe Gene Technology Co., Ltd, Beijing) and submitted to NCBI GenBank under accession No.  (MG763924). BeMYB680 have 1146bp open reading frame (ORF) that encodes a protein of 381 amino acids. . Transactivation analysis and subcellular localization assay revealed that BeMYB680 is a transcriptional activator and localized in the nucleus.  BeMYB680 was up-regulated when treated with ABA, PEG, NaCl, and H2O2; while down-regulated with Na2SO4 indicating its key role in abiotic stresses particularly to the best of our knowledge it is first time to clone BeMYB680form Bambusa emeiensis.
Keywords: BeMYB680; Bioinformatics; Transgenic; Abiotic stress; Bambusaemeiensis